Teachers' Beliefs and Attitudes Toward TPACK-Oriented Technology Integration for Quality Education: Developing Genially-Based Mathematics Learning Materials - Fitrani Dwina; Ayuni Kemala Safira; Widya Darwin; Yulyanti Harisman; Hafizatunnisa; Pipin Sumarni; Minora Longgom Nasution; Mazlini Adnan (Jurnal Penelitian Pendidikan IPA, 2026)
This study examines the beliefs and attitudes of high school mathematics teachers toward TPACK-oriented technology integration through the development of interactive teaching materials using Genially in Pesisir Selatan Regency. TPACK orientation is positioned as the foundation for integrating technological knowledge and mathematical content knowledge in the development of digital teaching materials. The study used a survey method with twenty mathematics teachers as participants. Data were collected through belief questionnaires, attitude questionnaires, and structured interviews to explain the reasons behind the questionnaire responses. Belief indicators include teachers' views on learning and knowledge for learning related to technology engagement. Attitude indicators include familiarity, interest, efforts to seek help when experiencing difficulties with features, and the desire to use Genially to support students' mathematical problem-solving during learning. The results showed very high acceptance of the use of technology, especially the Genially application (94–95% agreement on key indicators). Interviews confirmed that Genially's visual interactivity helps teachers explain abstract concepts and relate the material to real-life contexts, but internet stability and initial design time remain obstacles. These findings support Quality Education (SDG 4) by strengthening teachers' readiness to integrate technology in mathematics learning.